Shuttle running within a small-sided game: effects on internal and external workloads, in young elite soccer players - Panascì, M.; Ferrando, V.; Bisio, A.; Filipas, L.; Ruggeri, P.; Faelli, E. (International Journal of Sports Physiology and Performance, 2023)
Purpose: To compare the effects of 2 small-sided games (SSGs), shuttle running within the bout (SSG-S) versus possession play only (SSG-P) on acute physiological and metabolic responses, perception of effort, and performance.